Transcultural adaptation and validation of the Spanish version of the Identification of Functional Ankle Instability questionnaire (IdFAI-Sp) - Cervera-Garvi, Pablo; Ortega-Ávila, Ana Belén; Marchena-Rodríguez, Ana José; Gijón-Noguerón, Gabriel (Taylor & Francis, 2020)
Objective: The study aim was to cross-culturally adapt the Identification of Functional Ankle Instability (IdFAI) into a Spanish-language version (IdFAI-Sp), which would then be validated and its psychometric properties evaluated for use in possible cases of ankle instability. Methods: The cross-cultural adaptation was performed following the guidelines of the International Society for Pharmacoeconomics and Outcomes Research. Pearson correlations were calculated to assess the convergent validity between IdFAI and the Cumberland Ankle Instability Tool. Cronbach's alpha and test re-test reliability values were calculated and floor/ceiling effects analysed. Construct validity was assessed by confirmatory factor analysis (CFA). Results: The study population was composed of 110 participants, with a mean age of 40.49 years (10.43) and of whom 62 (56.36%) were female. Good test-retest results were obtained, with an intraclass correlation coefficient of 0.85 (ICC2,1: 95% CI: 0.82 - 0.88). The structure matrix was examined by CFA, which revealed a three-factor solution that accounted for 79.89% of the variance. The IdFAI-Sp obtained an excellent fit (RMSEA 0.068, GFI 0.94, CFI 0.98 and NFI 0.97). Conclusions: This study validates the IdFAI-Sp questionnaire, corroborating its value to researchers and medical professionals as a self-reported outcomes measure for use with a Spanish-speaking population.IMPLICATIONS FOR REHABILITATIONThe Spanish-language version of the Identification of Functional Ankle Instability questionnaire (IdFAI-Sp) is a valid and reliable tool.The IdFAI-Sp enables researchers and healthcare professionals to identify and classify chronic ankle instability among Spanish-speaking patients.Accordingly, it can be considered a useful clinical instrument.Aapplication of the questionnaire before and after treatment can reveal the patient's degree of recovery over time.
https://v2.sherpa.ac.uk/id/publication/20617
Keywords: Tobillos - Lesiones y heridas; Psicometría; Ankle instability; Reliability; Self-reported; Validity